The effect of task sequencing on second language written lexical complexity, accuracy, and fluency. (October 2019) - Allaw, Elissa; McDonough, Kim
Abstract: Planning and sequencing lessons in task-based language teaching has been considered a challenge because there is no agreed-upon theoretical framework for sequencing tasks. The SSARC model (stabilize, simplify, automatize, reconstruct, and complexify) of task sequencing allows for predictions about L2 learners' interlanguage development. However, previous task sequencing studies have reported mixed findings. Therefore, the current study further investigated the effectiveness of sequencing tasks using the SSARC model for promoting L2 written lexical complexity (e.g., lexical diversity), grammatical accuracy, and fluency. Novice French L2 writers ( N  = 42) at an elementary school in Lebanon carried out three experimental tasks in two different orders: simple-to-complex, and complex-to-simple. Pre-test and post-test measures of their written production and discrete point tests of target lexical and grammatical forms were administered. Results showed that the writers in both groups improved in terms of their lexical diversity, grammatical accuracy of relative clauses, and fluency, but the simple-to-complex group maintained the gains over time. Pedagogical implications for task sequencing in L2 contexts are discussed.